2011
DOI: 10.1107/s1600536811036981
|View full text |Cite
|
Sign up to set email alerts
|

Bis(9-aminoacridinium) bis(pyridine-2,6-dicarboxylato-κ3O2,N,O6)manganate(II) trihydrate

Abstract: The asymmetric unit of the title compound, (C13H11N2)2[Mn(C7H3NO4)2]·3H2O, consists of a discrete mononuclear [Mn(2,6-pydc)2]2− anionic complex (2,6-pydc is pyridine-2,6-dicarboxyl­ate) associated with two 9-amino­acridinium counter-ions for neutralization of charge and three uncoordin­ated water mol­ecules. The MnII atom is six-coordinated by (2,6-pydc)2− anions in a tridentate fashion and is at the centre of a distorted octa­hedron formed by the MnO4N2 bonding set. In the crystal, various inter­molecular int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Bond lengths and angles are comparable with those in similar structures (Tabatabaee et al, 2009;MacDonald et al, 2000;Aghabozorg et al, 2008;Harrison et al, 2006). Recently, our group reported a similar compound with Mn(II) as a metal center which has the same stochiometery as the title compound (Eshtiagh-Hosseini, Mirzaei, Eydizadeh et al, 2011 2). In Fig.…”
Section: S1 Commentsupporting
confidence: 77%
“…Bond lengths and angles are comparable with those in similar structures (Tabatabaee et al, 2009;MacDonald et al, 2000;Aghabozorg et al, 2008;Harrison et al, 2006). Recently, our group reported a similar compound with Mn(II) as a metal center which has the same stochiometery as the title compound (Eshtiagh-Hosseini, Mirzaei, Eydizadeh et al, 2011 2). In Fig.…”
Section: S1 Commentsupporting
confidence: 77%
“…These chains are attached to each other by three membered water cluster (Fig.3). In spite of the most recently observation which π-π interactions created between acridine moieties (Eshtiagh-Hosseini et al, 2011b), no π-π interaction between H9-Acr moieties is observed. Instead, such an interaction can be observed between anionic and cationic parts as seen in Fig.…”
Section: Methodsmentioning
confidence: 69%
“…The independent part of the unit cell of 2 contains an H-bonded contact ionic pair: the chloride anion and the protonated substituted acridine as a cation. According to a Cam-bridge Structural Database [43] search, the structure of 2 is one of many known examples of protonated acridine salts [44][45][46][47][48]. Note that in all these structures, the acridinium cation is nearly flat, while this is not the case for 2, where the angle between mean-squared planes composed of the carbon atoms of two lateral hydrocarbon rings is 21.6 (2) • .…”
Section: Single-crystal X-ray Diffraction Studies Of N 9 -Azidoacridinementioning
confidence: 99%